HUBUNGAN ADEKUASI HEMODIALISIS DAN STATUS GIZI DENGAN KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS DI RSUP SANGLAH DENPASAR - Putu Eka Mahayundhari; Ni Komang Wiardani; Lely Cintari (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2018)
Chronic Kidney Disease (CKD) is a disorder of renal function that is progressive and irreversible. One treatment of patients CKD is hemodialysis therapy. Hemodialysis patients are susceptible to malnutrition. If hemodialysis is inadequate and malnourished, it will decrease the patient's quality of life. The purpose of this study was to determine the relationship between adequation hemodialysis and nutritional status with the quality of life of patients CKD who undergoing hemodialysis at Sanglah Hospital. Type of observational research with cross sectional design. The sample of the study was 43 people who were consecutively. Data collected include sample, hemodialysis frequency, hemodialysis adequacy, nutritional status and quality of life. Data collected by interview and medical record data. A total of 35 samples (81.4%) of hemodialysis adequate were in adequate category, 33 samples (77%) nutritional status was in good category and 37 samples (86%) of quality survived in good category. From Spearman test, it is found that there is correlation between variable of hemodialysis adequation and nutritional status with quality of life of sample (p 0,05) which is strong and unidirectional. The conclusion of this research is there is relationship between adequation of hemodialysis and nutritional status with quality of life of PGK patients undergoing hemodialysis at Sanglah Hospital.Keyword: Chronic Kidney Disease, Hemodialysis Adequacy, Nutritional Status, Quality of Life